22.2k views
4 votes
Plzzzzzzzzzzzzz helpppppppppppppp

Plzzzzzzzzzzzzz helpppppppppppppp-example-1
Plzzzzzzzzzzzzz helpppppppppppppp-example-1
Plzzzzzzzzzzzzz helpppppppppppppp-example-2
User MANJEET
by
5.1k points

2 Answers

2 votes
Heyyyoooooooooo I got youuuuuu giveeee meeee a second pleaseeeeeee
User Supun De Silva
by
6.1k points
3 votes

Answer:

Question 25:


6

Question 19:


16

Explanation:

Question 25:


(x)/(12) + (y)/(3) = 2


(y)/(3 ) = 2 - (x)/(12)


y = 3( 2 - (x)/(12) )


y = 6 - (x)/(4)


y = - (x)/(4) + 6

Question 19:


{x}^(2) - 8x + c


{x}^(2) + c - 18

To find the c value ,


c = ( (b)/(2) {)}^(2)

divide the coefficient of x by 2 and square the result.


( - 1 * 4 {)}^(2)


( - 4 {)}^(2)


16

Hope it is helpful....

User Aerus
by
5.2k points